Relationships between different types of physical activity and metabolic syndrome among Taiwanese workers. Issue 1 (December 2017) - Huang, Jui-Hua; Li, Ren-Hau; Huang, Shu-Ling; Sia, Hon-Ke; Lee, Su-Shiang; Wang, Wei-Hsun; Tang, Feng-Cheng
Abstract This study aimed to investigate the relationships between different types of physical activity (PA) and metabolic syndrome (MetS). In this cross-sectional study, 3, 296 Taiwanese workers were enrolled. A self-reported questionnaire was used to assess nutritional health behavior and PA levels related to occupation, leisure time, and commuting. Anthropometric measures, blood pressure and biochemical determinations of the blood were also obtained. Multiple logistic regression was used to evaluate the adjusted odds ratios (ORs) and 95% confidence intervals (CI) of MetS and its components associated with different types of PA. The prevalence of MetS was 16.6% in workers. Compared with a low level of leisure-time PA, a high level of leisure-time PA showed a significantly lower risk of high triglycerides (OR 0.73, 95% CI 0.61–0.87) and MetS (OR 0.76, 95% CI 0.62–0.95). Compared with a low level of occupational PA, a high level of occupational PA represented a significantly lower risk of both abdominal adiposity (OR 0.64, 95% CI 0.49–0.84) and high triglycerides (OR 0.71, 95% CI 0.55–0.90). However, commuting PA levels were not significantly associated with MetS and its components. In conclusion, occupational PA as well as leisure-time PA could be important for the prevention of MetS.